Friction Welding of Fly Ash Reinforced AA6061 (P/M) Composite and Wrought Alloy (Journal of Manufacturing Engineering, 2008)
The aim of this study is to investigate the feasibility of joining fly ash reinforced AA6061 (P/M) composite to the AA6061 wrought alloy by rotational friction welding. The AA6061 composites, reinforced with 2, 4, 6, 8 and 10 wt% fly ash particles, were produced by powder metallurgy and hot extrusion techniques. The integrity of the joints has been investigated by optical microscopy, while the mechanical properties assessment was obtained by micro hardness. The results indicated that the P/M composite could be joined to AA6061 wrought alloy by friction welding. However, it was pointed out that the quality of the joint was affected negatively with the increase in weight percentage of the fly ash particles in the P/M composite.
Keywords: Composite Materials; Powder Metallurgy; Friction Welding